In vitro and in vivo studies of some new quinazolinone based compounds in breast cancer / Maryam Zahedi Fard - Maryam , Zahedi Fard (2016)
The synthesis of quinazolinone-Schiff bases compounds attracted great attention over the past few decades as an alternative mean to produce analogues of natural products. Quinazolinone compounds, sharing the main principal core structure, are currently announced in the clinical trials and pharmaceutical markets as anti-cancer agent. Therefore, there is a high clinical interest to identify new drugs that could be used to control the growth and expansion of cancer cells. In the present study, the cytotoxicity effect of some new quinazolinone compounds were tested on MDA-MB-231 and MCF-7 human breast cancer cell lines. This study also evaluated the induction of apoptosis by these compounds and their possible mechanisms of action on MCF-7 cell line. Cell Morphological changes, ROS generation, cytochrome c release, caspases activity and inhibition of NF-κB were also analyzed. MTT cytotoxicity test showed all five compounds demonstrated a potent anti-proliferative effect in MCF-7 cells, with IC50 value of a range of 3-6 μg/ml after 72 h of treatments. However, they showed no significant effect on MDA-MB-231 human breast cancer cell and MCF-10A human normal breast cell line compared to MCF-7 cell line. Most apoptosis morphological features in treated MCF-7 cells were observed by AO/PI staining. All compounds were found to possess a significant effect on perturbation in mitochondrial membrane potential and cytochrome c release from the mitochondria to the cytosol. They all triggered activation of caspase-9 and caspases-3/7 which imply the involvement of intrinsic pathways in the observed apoptosis. Compound 1, 2 and 3 also triggered expression of caspase-8 which exhibited the involvement of extrinsic pathway. However, treated MCF-7 cells with compounds 4 and 5 showed no activation of caspase-8 and nor suppression effect on NF-κB translocation, indicating the excluding of the involvement of extrinsic apoptosis pathway. Moreover, the toxicity assessment of quinazolinone compounds were also performed on the renal and hepatic function of ICR female mice at 250 mg/kg and the results revealed no adverse effects on the organ weight, body weight, serum biochemistry, and histopathology. Chemopreventive effect of compounds 2 and 4 against LA7-induced cancer in rats were also evaluated. The assessment of enzymatic antioxidants showed significant elevations of superoxide dismutase and catalase activities and a reduction in the level of malondialdehyde in treated groups. In addition, the histopathological assessments revealed that the rat mammary glands were protected from the carcinogenic effects of LA7 cells by compounds. Treatment with 2 and 4 also up regulated the expression of Bax and P53, however; down- regulated expression of Bcl-2 and PCNA in the breasts of LA7-induced rats in immunohistochemistry assay. Our results demonstrate a significant role of quinazolinone-based compounds as anti-proliferative agent toward human breast cancer which triggered apoptosis in vitro and in vivo.